2004
DOI: 10.1203/01.pdr.0000119366.21770.9e
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Heart Rate Characteristics Are Associated with Neonatal Mortality

Abstract: Estimating the risk of in-hospital mortality in the newborn intensive care unit can provide important information for healthcare providers, and illness severity scores have been devised to provide mortality risk estimates. Calculation of illness severity scores is time-consuming, and the information used to predict mortality is collected only for the first 12 to 24 h of life. A noninvasive continuous measure that uses information collected throughout the hospitalization and that requires no data entry could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…Projecting in vitro observations to heart function in situ, these findings account at least in part for reduced heart rate variability (8,30,31,38) and depressed cardiac function that accompanies sepsis (36,44). This may be particularly relevant to neonatal sepsis where mortality is often preceded by reduced heart rate variability and transient decelerations (10,11).…”
Section: Discussionmentioning
confidence: 96%
“…Projecting in vitro observations to heart function in situ, these findings account at least in part for reduced heart rate variability (8,30,31,38) and depressed cardiac function that accompanies sepsis (36,44). This may be particularly relevant to neonatal sepsis where mortality is often preceded by reduced heart rate variability and transient decelerations (10,11).…”
Section: Discussionmentioning
confidence: 96%
“…7 There has been a significant amount of research into altered HRV in neonates with changes in HRV preceding clinical markers for the diagnosis of sepsis in neonates, 18,19 as well as being predictive of mortality in this group of patients. 20,21 In adult patients, altered HRV has also been shown to be an early marker of the onset of multiple organ dysfunction 4 and has been shown to be predictive of outcome in head injury patients. 22,23 It has been shown that HRV decreases with sedation 24 and increases with sedation interruption.…”
Section: Discussionmentioning
confidence: 99%
“…The index was externally validated at Wake Forest University in a similar number of infants and was again shown to be highly correlated with diagnosis of sepsis [33,34]. Subsequent studies showed that a high HRC index ("HeRO score") is also correlated with mortality and with other infections and adds to laboratory values in the diagnosis of sepsis [35,36].…”
Section: Development Of the Hrc Index (Hero Score)mentioning
confidence: 97%